Thymoquinone with Metformin Decreases Fasting, Post Prandial Glucose, and HbA1c in Type 2 Diabetic Patients - Ali, Shoukath M.; Chen, Paul; Sheikh, Saifuddin; Ahmad, Ateeq; Ahmad, Moghis; Paithankar, Mahesh; Desai, Brijesh; Patel, Piyush; Khan, Mujtaba; Chaturvedi, Alok; Patel, Ronak; Panchal, Dharmendra T.; Shah, Kuntal; Chavda, Vipul; Saboo, Banshi D.; Patel, Alpesh; Ahmad, Imran (Drug Research, 2021)
Objective Antihyperglycemic activity of Thymoquinone (TQ) was evaluated in diabetic mouse model and patients.Methods TQ (50 mg/kg) was orally administered daily for 21 days in combination with metformin in diabetic mice and a reduction on blood glucose level was monitored. In human, a 90-day randomized study was carried out in 60 Type 2 Diabetes mellitus patients to evaluate safety and efficacy of TQ administration with metformin in a 3-arm study. Patients in arm 1 (T1) received 1 tablet of metformin SR 1000 mg and 1 tablet of TQ 50 mg once daily. The second arm (T2) patients received 1 tablet of metformin SR 1000 mg and 2 tablets of TQ 50 mg once daily. Patients in arm 3 (R) received 1 tablet of metformin SR 1000 mg only.Results The diabetic mice treated with combination of TQ and metformin showed significant decrease in blood sugar compared to those treated with only metformin. In patients who completed the study, the glycated hemoglobin (HbA1c) values in T1, T2 and R decreased after 3 months from 7.2, 7.2 and 7.3 to 6.7, 6.8, and 7.1, respectively. A greater reduction in Fasting Blood Glucose and Post Prandial Blood Glucose was also observed in T1 and T2 arms compared to R.Conclusion At dose levels of 50 and 100 mg of TQ combined with a daily dose of 1000 mg Metformin demonstrated a reduction in the levels of HbA1c and blood glucose compared to the standard treatment of diabetic patients with metformin alone.
Keywords: Nigella sativa; thymoquinone; diabetes mellitus; antihyperglycemic